Rural homestead reform in China: unveiling urbanization dynamics and lessons for sustainable development - Yahui, Liu; Qiming, Liu; Fangfang, Jiao (Frontiers in Sustainability, 2024)
The unique experience of land reform in China holds significant implications for other nations in urgent need of liberating and developing their productivity, providing valuable insights and lessons. This study conducted a micro-level analysis of land reform in China, the United States, and India, focusing on the implications for other nations. Surveys were conducted on 459 households in 12 townships in Zhejiang and Sichuan provinces, China. A random sampling approach was employed, selecting 5 sample counties (cities, districts) across Jinhua, Shaoxing, and Chengdu. Within each county (city, district), 2-3 townships were randomly selected, and 2-3 villages were chosen from each township. Subsequently, 10-20 households were randomly surveyed in each village. Statistical analysis using descriptive statistics and the Logistic model revealed robust results with P values below 0.05 for key variables.China's new urbanization strategy highlights the necessity of reforming the rural homestead system, particularly as higher urbanization rates prompt farmers to withdraw from and transfer their homesteads worldwide. Tailored homestead policies that consider regional disparities in urbanization levels are crucial. A micro-level survey underscores the impact of urbanization, household head identity, and age on farmers' decisions regarding homestead exit and transfer. Addressing external pressures, efforts should prioritize the revitalization of rural areas and the promotion of sustainable development. This includes enhancing small and medium-sized cities, fostering on-site urbanization, and creating nearby employment opportunities for farmers. However, the effectiveness of these measures varies across regions and is influenced by local levels of marketization. Internally, there is a need to bolster skill training and vocational education for farmers. In summary, the policy recommendations stemming from the micro-level survey in this study offer valuable insights for land reform strategies and sustainable development initiatives, spanning from individual farmers to national policies. They also contribute to a deeper understanding for policymakers, providing a novel analytical perspective.